Mixed support for a causal link between single dose intranasal oxytocin and spiritual experiences: opposing effects depending on individual proclivities for absorption - Cortes, Diana S (Soc Cogn Affect Neurosci, 2018)
Intranasal oxytocin (OT) has previously been found to increase spirituality, an effect moderated by OT-related genotypes. This pre-registered study sought to conceptually replicate and extend those findings. Using a single dose of intranasal OT vs placebo (PL), we investigated experimental treatment effects, and moderation by OT-related genotypes on spirituality, mystical experiences, and the sensed presence of a sentient being. A more exploratory aim was to test for interactions between treatment and the personality disposition absorption on these spirituality-related outcomes. A priming plus sensory deprivation procedure that has facilitated spiritual experiences in previous studies was used. The sample (N = 116) contained both sexes and was drawn from a relatively secular context. Results failed to conceptually replicate both the main effects of treatment and the treatment by genotype interactions on spirituality. Similarly, there were no such effects on mystical experiences or sensed presence. However, the data suggested an interaction between treatment and absorption. Relative to PL, OT seemed to enhance spiritual experiences in participants scoring low in absorption and dampen spirituality in participants scoring high in absorption.